2016
DOI: 10.1111/phn.12307
|View full text |Cite
|
Sign up to set email alerts
|

Living in Limbo: Latinas' Assessment of Lower Rio Grande Valley Colonias Communities

Abstract: Community asset mapping (CAM) is the collective process of identifying local assets and strategizing processes to address public health issues and concerns and improve quality of life. Prior to implementing a community‐based physical activity intervention with Latinas in the Texas Lower Rio Grande Valley, promotoras [community health workers] conducted 16 interactive sessions in 8 colonias. The analysis of the transcribed CAM recordings and on‐site observational data resulted in the construction of Living in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The idea of “public” encompasses the perceptions of identity that users have of resources that are not intended for proprietary or exclusive use, whether for financial or other reasons: “ If you have to pay, then it’s not really a [community] ” [ 91 ] (p. 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of “public” encompasses the perceptions of identity that users have of resources that are not intended for proprietary or exclusive use, whether for financial or other reasons: “ If you have to pay, then it’s not really a [community] ” [ 91 ] (p. 6).…”
Section: Resultsmentioning
confidence: 99%
“…"Safety concerns ranged from environmental hazards and limitations of the physical environment (e.g., few parks and green areas; poor maintenance of existing parks) to neighborhood threats (e.g., thefts, gangs, vandalism) and domestic violence." [91] (p. 5). "[ .…”
Section: Safety (Perceived and Objective)mentioning
confidence: 99%
“…Early research suggested U.S. colonias residents historically have been at risk for hepatitis, cholera, tuberculosis, dysentery and other waterborne disease due to poor water and sanitation (Hilfinger Messias et al, 2017). A 2000 study reported 89% prevalence of infection with the intestinal parasite Cryptosporidium parvum , the etiologic agent of cryptosporidiosis and Giardia lamblia , among children in seven Texas colonias (Leach et al, 2000).…”
Section: Water Insecurity Today In Us Coloniasmentioning
confidence: 99%
“…Poor environmental conditions in the region are connected to poor physical and mental health especially in the colonias, which are informal, unregulated periphery urban subdivisions (Hilfinger Messias et al 2017;Marquez-Velarde et al 2015;Mier et al 2008;O'Connor et al 2008). The term, colonia, means neighborhood or community in Spanish (Hilfinger Messias et al 2017).…”
Section: Environmental Concernsmentioning
confidence: 99%